2020
DOI: 10.3390/ijerph17207508
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Regional Water-Energy-Food Systems Based on Interval Number Multi-Objective Programming: A Case Study of Ordos, China

Abstract: Water, energy, and food are the most important basic resources for economic and social development. In the context of global population growth, environmental degradation, and resource shortages, the interrelationship between the water, energy, and food has become increasingly important. In this paper, the city of Ordos in China was selected as a study area. Firstly, this paper sorted out relevant research literature and fully understood the concept of water-energy-food (WEF) nexus. Then, an optimization model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Many scholars regard waterenergy-food (WEF) as a system (Bazilian et al, 2011;Dubreuil et al, 2013;Zhang & Vesselinov, 2017). With the rapid growth of the world economy, the demand for natural resources keeps rising, and it is expected that by 2030, the global demand for water, energy and food will increase by 30, 50, and 50%, respectively (Chen et al, 2020). However, water, energy, and food supply will face severe challenges due to the competition for land use (Haber, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars regard waterenergy-food (WEF) as a system (Bazilian et al, 2011;Dubreuil et al, 2013;Zhang & Vesselinov, 2017). With the rapid growth of the world economy, the demand for natural resources keeps rising, and it is expected that by 2030, the global demand for water, energy and food will increase by 30, 50, and 50%, respectively (Chen et al, 2020). However, water, energy, and food supply will face severe challenges due to the competition for land use (Haber, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research explored the interdependence of water, energy, and food systems, revealing that hydropower can jeopardize food production through several channels. These include competition for the same water resources, a rise in poverty, and the emission of greenhouse gases linked to climate change, resulting in a decline in agricultural production [68,[76][77][78][79][80]. It is important to highlight that negative social and environmental issues emerging or increasing in the context of hydropower construction can undermine people's perception regarding this energy source, which puts the necessary energy transition from more polluting sources to renewables at risk [81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the comprehensive evaluation index and coupling coordination level of the four subsystems of water resources, energy, food, and ecology in Dalad Banner are relatively low and have certain spatial differences. It is mainly restricted by the unbalanced development of towns and villages in Dalad Banner and the geographical environment conditions [61]. Dalad Banner is rich in mineral resources, but the development and coordination levels of its subsystems are different because of the different degrees of development and utilization in different townships.…”
Section: Discussionmentioning
confidence: 99%